Environmental Regulation, Promotion Pressure of Officials, and Enterprise Environmental Protection Investment - Chang, Ke-Chiun; Wang, Di; Lu, Yangyang; Chang, Wen; Ren, Guangqian; Liu, Li; Zhou, Xueya (Frontiers in Public Health, 2021)
This study expands on the impact of the local government environmental regulation on enterprise environmental protection investment. Furthermore, it also analyzes the influence of officials’ promotion pressure on enterprise environmental investment scale. The results show that the environmental protection investment of companies in China is generally insufficient. Companies’ attitude toward environmental protection is passive under the policy regulation, and the government's environmental supervision is still at a low level, which is far from the intention of the government. There is a U-shaped relationship between the pressure of official promotion and the scale of enterprise environmental protection investment. Only when the pressure of official promotion exceeds a certain limit can it positively stimulate enterprises to invest in environmental protection. Environmental regulation also exerts a threshold effect on enterprises environmental protection investment. This research provides a new way to understand the decision-making behavior of local officials and the environmental protection responsibility of enterprises. This study provides recommendations for improving the environment appraisal and government supervision system in China.